Genome-wide strand-specific UV mutagenesis in Escherichia coli is directed by the Mfd translocase - Ogün Adebali; Piotr A. Mieczkowski; Aziz Sancar; Christopher P. Selby (Proceedings of the National Academy of Sciences, 2025)
Transcription-coupled repair in Escherichia coli which is mediated by the Mfd translocase is responsible for higher repair rate in lacZ and lacI genes upon induction of transcription. Here, we analyze the entire E. coli genome for the effect of Mfd on UV-induced mutagenesis. We find genome-wide preferential repair of the transcribed strand (TS) over the nontranscribed strand (NTS), and consequently, fewer mutations are caused by cyclobutane pyrimidine dimers in the TS than the NTS, in a manner proportional to transcription rate. In mfd− cells, most mutations are in the TS, caused by RNA polymerase stalled at template strand damage inhibiting repair. These findings are pertinent to mfd − phenotypes involving gene expression, recombination, stationary phase mutagenesis, and drug resistance.